Comparative analysis and improvement of the 2-CSTRs anaerobic digestion system on biofuel production. (23rd February 2017) - Wan, Song; Li, Yongfeng
Abstract: A 2-CSTRs anaerobic digestion system using molasses wastewater as a biochemical substrate for fermentative bioenergy production and substrate degradation under various ethanol recovery rates was developed. The effects of ethanol recovery rates (0%–80%) and organic loading rates (OLRs; 8, 16 and 24 kgCOD m −3  d −1 ) on bioenergy production rate ( ε T ) and bioenergy production yield were examined, respectively. Since the system produced a significant amount of biofuels (i.e. hydrogen, methane and ethanol), the process performance in terms of energy conversion derived from the combination of three biofuels was calculated according to production rates and combustion heat values. Recycle and reflux are the two reuse approaches for effluents in the system. A maximum HPR of 1.34 (±0.7) mol d −1 and a maximum EPR of 0.45 (±0.4) mol d −1 were observed at the OLR of 24 kgCOD m −3  d −1 . Linear regression of the collection between HPR and EPR can be expressed as y = 0.3182x + 0.0114 (r 2  = 0.9853). The highest MPR of 0.45 (±0.07) mol d −1 was obtained at the original OLR of 24 kgCOD m −3  d −1, with an ethanol recover rate of 0%. Recycle resulted to a higher ε T and energy yield than reflux with the ethanol recover rate of 0% and 20%, respectively. This was equal to the ethanol recover rate of 50%, but lower than the ethanol recover rate of 80%; indicating that recycle would be more feasible for lower ethanol recover rates, and reflux may be more suitable with other kinds of ethanol recover rates. Highlights: A hierarchical split-phase anaerobic digestion for simultaneous biofuel is proposed. Energy production rate relies on recovery rate of ethanol. The choice of reuse way of effluent should be based on organic loading rates.